A hydrogel electrolyte, a preparation method thereof and a water-based zinc ion battery

CN122889856APending Publication Date: 2026-10-09FOSHAN POLYTECHNIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610849270.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-12
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]然而,传统的水凝胶电解质仍存在一些不足

Benefits of technology

(1)本发明通过亲水单体与多臂交联剂构建星形交联网络,以规整拓扑结构替代传统随机线型交联结构,使交联点分布、链段长度和应力传递路径更加均匀。该结构能够在提高凝胶压缩模量和抗穿刺能力的同时,避免因交联过密造成链段运动完全受限,从而改善力学性能与离子电导率难以兼顾的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application belongs to the technical field of batteries, and discloses a hydrogel electrolyte, a preparation method thereof and a water-based zinc ion battery. According to the application, the hydrogel electrolyte is prepared from the following raw materials in parts by mass: 5-20 parts of hydrophilic monomers, 0.5-5 parts of multi-arm crosslinking agents, 0.5-8 parts of nano clay, 0.5-10 parts of organic phosphonic acid, 5-30 parts of soluble zinc salt, 0.01-0.5 parts of photoinitiator and 0.5-5 parts of amino acid additive. The hydrophilic monomers include water-soluble monomers containing olefinic unsaturated bonds, and the multi-arm crosslinking agents include star-shaped macromolecules with three or more polymerizable end groups. The hydrogel electrolyte has excellent mechanical properties, ion conduction capacity and zinc negative electrode interface stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery technology, and specifically relates to a hydrogel electrolyte, its preparation method, and an aqueous zinc-ion battery. Background Technology

[0002] With the development of flexible wearable electronic devices, energy storage devices need to possess characteristics such as high safety, high flexibility, long cycle life, and environmental sustainability. Aqueous zinc-ion batteries, due to their advantages such as high theoretical specific capacity of zinc metal, low redox potential, abundant resources, and intrinsic safety, are considered to be a battery system with high application potential in the field of flexible energy storage.

[0003] Traditional aqueous zinc-ion batteries mostly use liquid aqueous electrolytes. While liquid electrolytes have good ion conductivity, they are prone to problems in practical use, such as leakage, poor flexibility, zinc anode dendrite growth, hydrogen evolution, corrosion, and dissolution of positive electrode active materials. These problems lead to increased battery polarization, capacity decay, and safety risks. Replacing liquid electrolytes with hydrogel electrolytes is an important technical approach to reduce leakage risk, improve flexibility, and enhance the stability of the zinc anode interface.

[0004] However, traditional hydrogel electrolytes still have some shortcomings. First, it is difficult to balance mechanical properties and ionic conductivity. Synthetic polymer hydrogels, such as polyacrylamide and polyacrylic acid, usually rely on crosslinking density to improve mechanical strength, but a high crosslinking density will restrict chain segment movement and ion migration; while a low crosslinking density is beneficial for ion conduction, it will lead to insufficient gel strength, making it difficult to resist zinc dendrite puncture and repeated bending stress.

[0005] Secondly, nanoclay is difficult to disperse stably in high-concentration zinc salt environments. Nanoclay can form a colloidal dispersion in water, where the negative charge of its lamellar layers helps guide the uniform deposition of zinc ions and enhances the gel's mechanical properties. However, upon adding soluble zinc salts, the zinc ions shield the negative charge on the clay lamellar surface, compressing the electric double layer and weakening the electrostatic repulsion between the lamellar layers, leading to flocculation or agglomeration of the nanoclay. Flocculated clay cannot effectively participate in physical cross-linking and may even form stress concentration points, thereby weakening the mechanical enhancement and dendrite suppression effects.

[0006] Third, traditional hydrogel electrolytes typically rely on a single physical barrier or electrostatic shielding mechanism to suppress zinc dendrites, which makes it difficult to effectively regulate zinc deposition behavior. This results in insufficient cycle life of zinc symmetric batteries, making it difficult to meet the application requirements of long-life flexible energy storage devices.

[0007] Therefore, there is an urgent need to provide a hydrogel electrolyte that can simultaneously improve mechanical properties, ion conductivity, and the stability of the zinc anode interface. Summary of the Invention

[0008] The present invention aims to at least solve one of the technical problems existing in the prior art. Therefore, one objective of the present invention is to provide a hydrogel electrolyte with excellent mechanical properties, ion conductivity, and zinc anode interface stability.

[0009] The second objective of this invention is to provide a method for preparing the above-mentioned hydrogel electrolyte.

[0010] A third objective of this invention is to provide an aqueous zinc-ion battery comprising the above-mentioned hydrogel electrolyte.

[0011] The fourth objective of this invention is to provide a flexible wearable electronic device comprising the above-mentioned hydrogel electrolyte.

[0012] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a hydrogel electrolyte, wherein the raw materials for preparing the hydrogel electrolyte, by weight parts, include: 5-20 parts of hydrophilic monomer, 0.5-5 parts of multi-arm crosslinking agent, 0.5-8 parts of nano-clay, 0.5-10 parts of organophosphonic acid, 5-30 parts of soluble zinc salt, 0.01-0.5 parts of photoinitiator, and 0.5-5 parts of amino acid additives; wherein the hydrophilic monomer includes a water-soluble monomer containing an olefinic unsaturated bond, and the multi-arm crosslinking agent includes a star-shaped macromolecule having three or more polymerizable end groups.

[0013] In the hydrogel electrolyte, the organophosphonic acid is adsorbed on the sheet surface of the nanoclay, and the hydrophilic monomer and the multi-arm crosslinking agent are free radically polymerized to form a star-shaped crosslinking network. The nanoclay is dispersed in the star-shaped crosslinking network and forms a dynamic physical crosslinking network with the star-shaped crosslinking network. The amino acid additive and the organophosphonic acid form a synergistic network through hydrogen bonds, which jointly regulates the zinc ion solvation structure and forms a composite adsorption layer on the zinc anode surface.

[0014] In the hydrogel electrolyte, hydrophilic monomers undergo photo-initiated free radical polymerization to form a polymer backbone. A multi-arm crosslinking agent participates in the polymerization reaction with three or more polymerizable end groups, thereby forming a star-shaped crosslinked network with the multi-arm crosslinking agent as the central core and multiple arms extending outwards. This star-shaped crosslinked network differs from the random inter-chain crosslinked network formed by traditional linear bifunctional crosslinking agents; its crosslinking points are more concentrated and the chain segment lengths are more uniform, which helps reduce local stress concentration and retains a certain degree of chain segment mobility while maintaining network integrity.

[0015] The nano-clay is dispersed in the star-shaped cross-linked network. The silanol groups on the surface of its sheets can form reversible hydrogen bonds or physical adsorption with the hydrophilic polymer segments, the ether oxygen groups or amide groups of the multi-arm cross-linking agent, forming dynamic physical cross-linking points. These dynamic physical cross-linking points can undergo reversible dissociation and reconstruction when the gel is compressed, stretched or bent. On the one hand, this improves the gel's modulus, puncture resistance and dendrite puncture resistance; on the other hand, it maintains the gel's flexibility and elongation at break through energy dissipation.

[0016] Organophosphonic acids are adsorbed onto the surface of nano-clay sheets. Their phosphonic acid groups can chelate, hydrogen bond, and interact with the surface of the clay sheets, forming a steric hindrance layer between the sheets. This reduces the shielding effect of zinc ions on the negative charge of the clay sheet surface, maintains the repulsion between the sheets and colloidal stability, and prevents irreversible flocculation or the formation of large-sized agglomerates in the nano-clay.

[0017] Furthermore, organophosphonic acids are not only used as clay dispersants; the -P=O or -P-OH sites in their phosphonic acid groups can also form reversible coordination sites with zinc ions. The ether oxygen or amide sites in multi-arm crosslinking agents form a three-dimensional array within the star-shaped network. These two types of sites are interconnected within the gel network, allowing zinc ions to adsorb, dissociate, and hop between phosphonic acid coordination sites, ether oxygen sites, or amide sites, forming a relay conduction channel with low migration resistance. This improves the mechanical strength of the gel while maintaining high ionic conductivity.

[0018] Furthermore, organophosphonic acids can adsorb onto the zinc anode surface, forming an interface regulation layer containing phosphonic acid groups. This interface regulation layer can cover the highly active sites on the zinc anode surface, reducing the probability of water molecules directly contacting the zinc anode, thereby inhibiting hydrogen evolution and corrosion side reactions. Simultaneously, its coordination with zinc ions can regulate the desolvation process and nucleation behavior of zinc ions at the anode interface. The negative charge on the surface of the nanoclay sheets can homogenize the zinc ion flux at the interface, limiting sudden increases in local current density. Together, these two elements form a dual dendrite suppression mechanism of "interface nucleation regulation + zinc ion flux homogenization."

[0019] Amino acid additives (such as β-alanine and proline) contain both amino (-NH2) and carboxyl (-COOH) groups. The amino group can form intermolecular hydrogen bonds with the phosphonic acid groups of organophosphonic acids, constructing an "organophosphonic acid-amino acid" hydrogen bond network, further stabilizing clay dispersion and synergistically regulating the zinc ion solvation structure. The carboxyl group can form weak coordination with zinc ions, supplementing the zinc ion conduction channels and forming a relay jumping system with the phosphonic acid coordination sites of organophosphonic acids. Simultaneously, amino acids can also undergo chemisorption on the zinc anode surface, forming a denser composite interfacial protective layer with organophosphonic acids, enhancing the inhibition of hydrogen evolution and corrosion.

[0020] Preferably, the hydrophilic monomer comprises one or more selected from acrylamide, N-hydroxyethylacrylamide, N-isopropylacrylamide, acrylic acid, and alkali metal salts of acrylic acid. More preferably, it comprises one or more selected from acrylamide, N-hydroxyethylacrylamide, N-isopropylacrylamide, and sodium acrylate. The above monomers contain hydrophilic groups such as amide groups, hydroxyl groups, or carboxyl groups, which are beneficial for forming hydrogel networks and can provide sites for weak interactions with zinc ions or nanoclay.

[0021] Preferably, the amount of the hydrophilic monomer is 8-10 parts. When the amount of hydrophilic monomer is less than 5 parts, the polymer backbone content is insufficient, the continuity and self-supporting ability of the gel network are poor, and problems such as insufficient strength, difficulty in film formation, or damage during battery assembly are likely to occur. When the amount is more than 20 parts, the viscosity of the system increases significantly, which is not conducive to the uniform dispersion of nano-clay and precursor injection. At the same time, too many polymer chain segments will weaken the space for ion migration in the aqueous phase, resulting in a decrease in ionic conductivity. When its amount is preferably controlled at 8-10 parts, a good aqueous ion conduction environment can be maintained while forming a complete backbone network, so that the gel has strength, flexibility, and conductivity.

[0022] Preferably, the multi-arm crosslinking agent includes one or more of multi-arm polyethylene glycol acrylate, multi-arm polyethylene glycol methacrylate, and multi-arm acrylamide derivatives. Compared with conventional bifunctional crosslinking agents such as N,N-methylenebisacrylamide or linear PEGDA, the multi-arm crosslinking agent can simultaneously connect multiple polymer chains at a single molecular center, forming a radial topology. This results in a more regular distribution of crosslinking points, more uniform stress transmission, and reduces the embrittlement tendency caused by excessively dense local crosslinking in traditional random crosslinking networks.

[0023] Preferably, the multi-arm crosslinking agent is a 4-arm, 6-arm, or 8-arm polyethylene glycol acrylate with a weight-average molecular weight of 2000–20000 Da; or, the multi-arm crosslinking agent is a multi-arm acrylamide derivative without ester bonds. Using a 4-arm, 6-arm, or 8-arm structure achieves a good balance between crosslinking efficiency, network uniformity, and precursor solubility. When the weight-average molecular weight is below 2000 Da, the arm chains are too short, the network is too rigid, and the ion channel space is insufficient. When the weight-average molecular weight is above 20000 Da, the crosslinking point spacing is too large, resulting in decreased gel strength and dimensional stability.

[0024] More preferably, the multi-arm crosslinking agent is a 4-arm polyethylene glycol-acrylamide. This crosslinking agent provides reversible coordination migration sites for zinc ions through the ether bond oxygen in the polyethylene glycol segments. On the other hand, because it does not contain easily hydrolyzable ester bonds, it is not prone to hydrolytic chain scission or crosslinking point failure in aqueous zinc salt systems and long-term electrochemical cycling environments, which is beneficial to improving the structural retention rate and long-term cycling stability of the gel electrolyte.

[0025] Preferably, the amount of the multi-arm crosslinking agent is 1 to 1.5 parts. When the amount of the multi-arm crosslinking agent is less than 0.5 parts, the number of star-shaped crosslinking points is insufficient, and the gel may have problems such as insufficient crosslinking, poor self-support, and low compressive modulus. When the amount is more than 5 parts, the network crosslinking is too dense, the chain segment movement is excessively restricted, the gel brittleness increases, and the elongation at break and ionic conductivity may decrease. When its amount is preferably controlled at 1 to 1.5 parts, a stable but not excessively dense star-shaped network can be formed, which better balances mechanical strength, ion migration space, and flexible adaptability.

[0026] Preferably, the nanoclay is a two-dimensional layered silicate mineral with water-swellable dispersibility, including one or two of lithium saponite and organobentonite. The nanoclay has a high aspect ratio, negative surface charge on its layers, and silanol sites, enabling it to simultaneously perform mechanical reinforcement, dynamic cross-linking, zinc ion flux homogenization, and stress dissipation within the gel network. Lithium saponite and organobentonite can disperse in water to form a transparent colloidal solution. Lithium saponite is more preferably preferred.

[0027] Preferably, the amount of nanoclay used is 1.5 to 2 parts. When the amount of nanoclay is less than 0.5 parts, the number of lamellar layers is insufficient, making it difficult to form an effective dynamic physical cross-linking network, and the improvement on gel modulus, puncture resistance, and zinc deposition uniformity is limited. When the amount is more than 8 parts, even with the stabilizing effect of organophosphonic acid, the high solid content of the system may lead to problems such as excessive viscosity, local agglomeration, and obstructed ion migration pathways. When its amount is preferably controlled at 1.5 to 2 parts, the nanoclay can be more fully distributed in the star-shaped network, forming continuous reinforcing and flux-regulating sites, while not significantly affecting ion conductivity.

[0028] Preferably, the organophosphonic acid includes one or more of ethylenediaminetetramethylenephosphonic acid, hydroxyethylidene diphosphonic acid, aminotrimethylenephosphonic acid, and 2-phosphonobutane-1,2,4-tricarboxylic acid. More preferably, the organophosphonic acid includes one or more of ethylenediaminetetramethylenephosphonic acid, hydroxyethylidene diphosphonic acid, and aminotrimethylenephosphonic acid.

[0029] The organophosphonic acid has at least three functions in this invention. First, it adsorbs onto the surface of the nano-clay sheets before the addition of zinc salt, utilizing the chelating and electrostatic effects of the phosphonic acid groups to improve the repulsive stability between the sheets, and forming steric hindrance through the molecular skeleton, thereby inhibiting zinc salt-induced flocculation. Second, its -P=O and -P-OH groups form reversible coordination sites with zinc ions, and together with the ether oxygen or amide group sites of the multi-arm crosslinking agent, they constitute a zinc ion relay conduction network. Third, it can adsorb onto the zinc anode surface, reducing the exposure of side-reactive active sites and regulating the zinc ion desolvation and nucleation processes.

[0030] Preferably, the amount of organophosphonic acid used is 2-3 parts. When the amount is less than 0.5 parts, it is difficult to fully cover the surface of the nano-clay sheets, and the clay may still flocculate after the addition of zinc salt. At the same time, the interface regulation and ion channel construction effects are insufficient. When the amount is more than 10 parts, the excess phosphonic acid groups may excessively complex with zinc ions, reducing the proportion of migratable zinc ions and causing excessive changes in the acidity or ionic environment of the system, which is not conducive to electrochemical stability. When the amount is controlled at 2-3 parts, a better balance can be achieved between clay stability, zinc ion migration, and zinc anode interface regulation.

[0031] Preferably, the amino acid additive includes one or more of alanine, β-alanine, proline, valine, glycine, lysine, and 6-aminohexanoic acid; more preferably, it is β-alanine or proline. The amino group (-NH2) in the amino acid molecule can form a hydrogen bond network with the phosphonic acid group of the organophosphonic acid, synergistically regulating the zinc ion solvation structure; the carboxyl group (-COOH) can form a weak coordination with zinc ions, supplementing the zinc ion conduction channel; at the same time, the amino acid has an adsorption effect on the zinc anode surface, forming a denser interfacial protective layer together with the organophosphonic acid. Experimental verification shows that adding 0.5-2% β-alanine can increase the ionic conductivity by 10-15%, further extending the cycle life of the zinc symmetric battery.

[0032] Preferably, the amount of the amino acid additive is 1 to 3 parts. When the amount is less than 0.5 parts, the synergistic effect is not obvious; when the amount is more than 5 parts, it may affect the crosslinking uniformity of the gel or increase the cost.

[0033] Preferably, the soluble zinc salt comprises one or more of zinc sulfate, zinc acetate, zinc trifluoromethanesulfonate, zinc chloride, and zinc nitrate. The soluble zinc salt provides the Zn required for battery cycling. 2+ Its concentration affects not only the ionic conductivity and zinc ion transference number of the gel electrolyte, but also the degree to which zinc salts disturb the dispersion stability of nanoclay.

[0034] Preferably, the amount of the soluble zinc salt is 10 to 30 parts. Within this preferred range, the system can generally provide a sufficient zinc ion concentration and maintain low battery polarization; if the amount is too low, the zinc ion concentration is insufficient, and the ionic conductivity and rate performance decrease; if the amount is too high, the ionic strength of the system is too high, which may induce salting out, decrease clay stability, deteriorate low-temperature performance, or abnormal gel hydration.

[0035] Preferably, the photoinitiator is a water-soluble ultraviolet photoinitiator, including one or two of lithium phenyl-2,4,6-trimethylbenzoylphosphonite and 2-hydroxy-1-(4-(2-hydroxyethoxy)phenyl)-2-methyl-1-propanone.

[0036] Preferably, the amount of photoinitiator is 0.1 to 0.12 parts. When the amount of photoinitiator is less than 0.01 parts, insufficient free radical generation can easily lead to incomplete polymerization and insufficient gel solidification; when the amount is more than 0.5 parts, residual initiator or photolysis byproducts may affect electrochemical stability. Preferably controlling its amount to 0.1 to 0.12 parts is beneficial for obtaining a uniformly solidified gel within a shorter light exposure time, while reducing the impact of residues on battery performance.

[0037] In a second aspect, the present invention provides a method for preparing the above-mentioned hydrogel electrolyte, comprising the following steps: Nano-clay, water, and organophosphonic acid were mixed and stirred to disperse, resulting in an organophosphonic acid-clay composite dispersion. The organophosphonic acid-clay composite dispersion was mixed with soluble zinc salt, hydrophilic monomer, multi-arm crosslinking agent, amino acid additive, and photoinitiator, and stirred to obtain a precursor solution. The precursor solution was cured under ultraviolet light to obtain the hydrogel electrolyte.

[0038] Preferably, the method for preparing the hydrogel electrolyte includes the following steps: Step S1: Add nano-clay to water and stir to disperse for 1-4 hours to obtain a clay dispersion. Step S2: Add organophosphonic acid to the clay dispersion and continue stirring for 0.5 to 1 hour to allow the organophosphonic acid to be fully adsorbed onto the surface of the nano-clay sheets, forming an organophosphonic acid-clay composite dispersion. Step S3: Add soluble zinc salt, hydrophilic monomer, multi-arm crosslinking agent and amino acid additive to the organophosphonic acid-clay composite dispersion, and stir for 1-3 hours to obtain a mixture; Step S4: Add a photoinitiator to the mixture and stir in the dark for 0.5 to 1 hour to obtain a precursor solution; Step S5: The precursor solution is cured by ultraviolet light to obtain the hydrogel electrolyte.

[0039] Specifically, this invention first disperses nano-clay, allowing for thorough hydration and exfoliation of the sheets; then, organophosphonic acid is added, enabling phosphonic acid groups to preferentially occupy adsorption sites on the clay surface and form a stable protective layer around the sheets. Adding soluble zinc salt after forming this stable protective layer significantly reduces the risk of flocculation caused by zinc ions directly compressing the electric double layer of the clay sheets. If the zinc salt is added prematurely, or simultaneously with the nano-clay and organophosphonic acid, the negative charge on the clay sheet surface may be shielded by zinc ions, making it difficult for the organophosphonic acid to fully exert its pre-stabilizing effect. Amino acid additives can be added together with other components in step S3; their amino and carboxyl groups form hydrogen bonds and coordinate synergistically with the organophosphonic acid and polymer network during subsequent photocuring.

[0040] Preferably, the wavelength of the ultraviolet curing is 300–400 nm, and the light intensity is 50–500 mW / cm². 2 The illumination time is 1–60 min. Insufficient light intensity or too short an illumination time results in insufficient polymerization conversion, decreased gel strength, and reduced dimensional stability; excessive light intensity or too long an illumination time may lead to localized heating, excessive free radicals, or uneven network shrinkage. Using the above range is beneficial for obtaining uniform, rapid, and in-situ moldable hydrogel electrolytes.

[0041] Preferably, the precursor solution can be injected into the battery casing, cast onto the electrode surface, or injected into a mold and then cured under ultraviolet light.

[0042] In a third aspect, the present invention provides an aqueous zinc-ion battery comprising the above-described hydrogel electrolyte.

[0043] Preferably, the aqueous zinc-ion battery further includes a positive electrode and a negative electrode. The negative electrode can be zinc foil, zinc sheet, zinc powder coating, or a zinc alloy negative electrode, and the positive electrode can be a conventional positive electrode for aqueous zinc-ion batteries. Because the hydrogel electrolyte possesses high mechanical strength, high ionic conductivity, good flexibility, and excellent zinc negative electrode interface stability, the aqueous zinc-ion battery is particularly suitable for use in flexible electronic devices and wearable electronic devices.

[0044] In a fourth aspect, the present invention provides a flexible wearable electronic device comprising the aforementioned aqueous zinc-ion battery.

[0045] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention constructs a star-shaped cross-linked network by using hydrophilic monomers and multi-arm cross-linking agents, replacing the traditional random linear cross-linked structure with a regular topological structure, making the distribution of cross-linking points, chain segment length, and stress transmission path more uniform. This structure can improve the gel compression modulus and puncture resistance while avoiding the complete restriction of chain segment movement caused by excessive cross-linking, thereby improving the problem of difficulty in balancing mechanical properties and ionic conductivity.

[0046] (2) In this invention, organophosphonic acid is pre-adsorbed onto the surface of nano-clay before the addition of zinc salt. This utilizes chelation, electrostatic interaction, and steric hindrance to suppress zinc salt-induced clay flocculation, enabling the nano-clay to maintain uniform dispersion in a high-ionic-strength zinc salt system. Therefore, the dynamic physical cross-linking, stress dissipation, and zinc ion flux homogenization effects of the nano-clay can be fully utilized, avoiding the low reinforcing efficiency and performance fluctuations caused by agglomeration in existing nano-clay composite gels.

[0047] (3) In this invention, the phosphonic acid group of the organophosphonic acid forms a hydrogen bond network with the amino group of the amino acid additive, which jointly regulates the solvation structure of zinc ions; the carboxyl group of the amino acid and the -P=O / -P-OH group of the organophosphonic acid form a relay coordination system, which enables zinc ions to migrate continuously between more weak coordination sites, further reducing the migration energy barrier; at the same time, the amino acid can generate an electrostatic shielding effect on the zinc anode surface, preferentially adsorbing at the deposition tip and inducing uniform nucleation. The synergistic effect of organophosphonic acid and amino acid additive significantly improves ionic conductivity, zinc ion transport number and cycle life.

[0048] (4) This invention forms a multiple dendrite suppression mechanism through interfacial adsorption of organophosphonic acids, negative charge shielding of nano-clay, and electrostatic shielding of amino acid tips. Organophosphonic acids can reduce the side reaction activity on the zinc anode surface and regulate the nucleation behavior of zinc ions; nano-clay can homogenize the zinc ion flux and inhibit the formation of local deposition tips; amino acids can preferentially adsorb at deposition protrusions and induce secondary nucleation. The combination of these three can significantly reduce the risk of dendrites piercing the gel or separator, and greatly improve the cycle life of zinc symmetric cells and the entire cell. Detailed Implementation

[0049] To enable those skilled in the art to more clearly understand the technical solutions described in this invention, the following embodiments are provided for illustration. It should be noted that the following embodiments do not constitute a limitation on the scope of protection claimed by this invention.

[0050] Unless otherwise specified, the raw materials, reagents or devices used in the following examples are available from conventional commercial sources or can be obtained by existing known methods.

[0051] The specific information of some raw materials in the following embodiments is shown in Table 1 below.

[0052] Table 1

[0053] Example 1 This embodiment provides a hydrogel electrolyte, whose raw material components, by weight, include: 8 parts acrylamide, 1.5 parts 4-arm-polyethylene glycol-acrylamide, 2 parts lithium saponite, 3 parts ATMP (50% aqueous solution, equivalent to 1.5 parts pure ATMP), 1 part β-alanine, 20 parts zinc sulfate, 0.12 parts LAP, and 64.38 parts deionized water.

[0054] The preparation method of the above-mentioned hydrogel electrolyte is as follows: Step S1: Slowly add lithium saponite powder to deionized water and stir at 800 rpm for 2 hours at room temperature to obtain clay dispersion. Step S2: Add ATMP to the above clay dispersion and continue stirring for 0.5 h to allow ATMP to be adsorbed onto the surface of lithium saponite sheets through phosphonic acid groups, thus obtaining an organophosphonic acid-clay composite dispersion. Step S3: Add zinc sulfate, acrylamide, 4-arm-polyethylene glycol-acrylamide and β-alanine to the above organophosphonic acid-clay composite dispersion, stir for 1.5 h to obtain a mixture; Step S4: Add photoinitiator LAP to the above mixture and stir in the dark for 0.5 h to obtain the precursor solution; Step S5: Pour the above precursor solution into a glass mold (solution thickness 1 mm), and use a 365 nm LED light source at 200 mW / cm². 2 The hydrogel electrolyte was cured by irradiation with light intensity for 15 minutes.

[0055] Example 2 This embodiment provides a hydrogel electrolyte, whose raw material components, by weight, include: 10 parts N-hydroxyethyl acrylamide, 1 part 4-arm-polyethylene glycol-acrylamide, 1.5 parts lithium saponite, 2 parts ATMP (50% aqueous solution, equivalent to 1 part pure ATMP), 1 part β-alanine, 20 parts zinc sulfate, 0.1 parts LAP, and 64.4 parts deionized water.

[0056] The preparation method is the same as in Example 1.

[0057] Example 3 This embodiment provides a hydrogel electrolyte, whose raw material components, by weight, include: 5 parts acrylamide, 0.5 parts 4-arm-polyethylene glycol-acrylamide, 0.5 parts lithium saponite, 1 part ATMP (50% aqueous solution, equivalent to 0.5 parts pure ATMP), 0.5 parts proline, 5 parts zinc sulfate, 0.02 parts LAP, and 87.48 parts deionized water.

[0058] The preparation method is the same as in Example 1.

[0059] Example 4 This embodiment provides a hydrogel electrolyte, whose raw material components, by weight, include: 20 parts acrylamide, 5 parts 4-arm-polyethylene glycol-acrylamide, 8 parts lithium saponite, 20 parts ATMP (50% aqueous solution, equivalent to 10 parts pure ATMP), 5 parts β-alanine, 30 parts zinc sulfate, 0.5 parts LAP, and 11.5 parts deionized water.

[0060] The preparation method is the same as in Example 1.

[0061] Comparative Example 1 The only difference from Example 1 is that ATMP is missing, and the missing amount is made up by deionized water; the other raw material components, amounts and preparation methods are the same as in Example 1.

[0062] Comparative Example 2 The only difference from Example 1 is that lithium saponite is missing, and the missing amount is made up by deionized water; the other raw material components, amounts and preparation methods are the same as in Example 1.

[0063] Comparative Example 3 The only difference from Example 1 is that polyethylene glycol diacrylate is used to replace the 4-arm polyethylene glycol acrylamide in equal amounts; the other raw material components, dosages, and preparation methods are the same as in Example 1.

[0064] Comparative Example 4 The only difference from Example 1 is that β-alanine is not added, and the missing amount is made up by deionized water; the other raw material components, amounts and preparation methods are the same as in Example 1.

[0065] Comparative Example 5 The raw material components use conventional linear crosslinking agent BIS and do not contain organophosphonic acid, nano clay, amino acid additives, or multi-arm crosslinking agents.

[0066] By weight, the raw material components include: 10 parts acrylamide, 0.1 parts N,N-methylenebisacrylamide, 20 parts zinc sulfate, 0.1 parts LAP, and 69.8 parts deionized water.

[0067] The preparation method is as follows: mix the above raw material components, stir evenly, and then perform conventional ultraviolet curing.

[0068] Performance testing (1) Ionic conductivity test: AC impedance testing was performed using an electrochemical workstation with a frequency range of 1MHz to 1Hz, a perturbation voltage of 10mV, and a test temperature of 25℃. The hydrogel electrolyte was clamped between two stainless steel blocking electrodes, and the Nyquist plot was recorded. The bulk resistance Rb was obtained by reading the intersection of the high-frequency region and the real axis, and the ionic conductivity was calculated using the formula σ=d / (Rb×A), where d is the gel thickness and A is the electrode area. Each sample was tested 3 times and the average value was taken.

[0069] (2) Zinc symmetric battery cycle test: Assemble CR2032 coin cells with a structure of zinc foil (0.1 mm thick, 12 mm diameter) || hydrogel electrolyte (1 mm thick, 16 mm diameter) || zinc foil. Constant current charge-discharge tests were performed using a LAND battery testing system at a current density of 1 mA / cm². 2 The surface capacity is 1mAh / cm². 2Record the cycle life and overpotential during stable cycling. Assemble at least three parallel cells for each sample and take the average value.

[0070] (3) Mechanical property testing: Mechanical properties were tested using a universal testing machine. For compression testing, cylindrical gel samples were used, with a diameter of 10 mm and a height of 5 mm. The compression rate was 5 mm / min, and the compressive modulus at 50% strain was recorded. For tensile testing, dumbbell-shaped gel specimens were used, with a tensile rate of 50 mm / min, and the elongation at break was recorded. Each sample was tested 5 times, and the average value was taken.

[0071] The hydrogel electrolytes prepared in each embodiment and comparative example were tested according to the above test method. The test results are shown in Table 2 below.

[0072] Table 2

[0073] As shown in Table 2, the hydrogel electrolytes of Examples 1-4 of this invention exhibit high ionic conductivity of 13.8–18.2 mS / cm, a zinc symmetric battery cycle life of 700–900 h, low overpotential of 20–28 mV, a compressive modulus of 218–270 kPa, and an elongation at break of 560–720%. These results demonstrate that, through the combined action of multi-arm crosslinking agents, nanoclay, organophosphonic acids, and amino acids, this invention enables the hydrogel electrolyte to simultaneously achieve high ionic conductivity, high mechanical strength, and good flexibility.

[0074] In Comparative Example 1 (without organophosphonic acid), the clay agglomerated in the presence of zinc salt, with a compressive modulus of only 80 kPa, an ionic conductivity of 11.0 mS / cm, and a cycle life of 430 hours. In Example 1 (with ATMP), the clay was uniformly dispersed, with the compressive modulus increasing to 270 kPa (an increase of 238%), the ionic conductivity increasing to 18.2 mS / cm (an increase of approximately 65%), and the cycle life increasing to 900 hours (an increase of approximately 109%). This demonstrates that organophosphonic acid effectively inhibits zinc salt-induced clay flocculation, achieving a synergistic enhancement effect of "reinforcing without sacrificing conductivity".

[0075] Comparative Example 2 (without nanoclay) had a compressive modulus of only 75 kPa and an elongation at break of only 85% (high gel brittleness); Example 1 (containing lithium saponite) achieved a compressive modulus of 270 kPa (an increase of 260%), an elongation at break of 720% (an increase of approximately 747%), and a cycle life that increased from 480 h to 900 h (an increase of approximately 88%). This indicates that the introduction of nanoclay not only significantly enhanced the mechanical properties of the gel but also greatly improved its flexibility, while effectively inhibiting zinc dendrite growth.

[0076] Comparative Example 3 used linear PEGDA as a crosslinking agent, exhibiting an ionic conductivity of only 9.5 mS / cm, a compressive modulus of 100 kPa, and a cycle life of 460 hours. Example 1 used a multi-arm crosslinking agent, achieving an ionic conductivity of 18.2 mS / cm, a compressive modulus of 270 kPa, and a cycle life of 900 hours. This demonstrates that the multi-arm star-shaped crosslinking network, compared to the linear PEGDA crosslinking network, can more effectively break the trade-off between mechanical properties and ionic conductivity, while significantly improving cycle stability.

[0077] Comparative Example 4 (without amino acids) had a conductivity of 12.0 mS / cm and a cycle life of 550 h; while Example 1 (with β-alanine added) increased the conductivity to 18.2 mS / cm, extended the cycle life to 900 h, and reduced the overpotential from 42 mV to 20 mV. This directly demonstrates that the amino group of amino acids forms a hydrogen bond network with the phosphonic acid group of organophosphonic acids, and the carboxyl group provides additional Zn. 2+ The coordination sites significantly optimized the ion jumping channels; at the same time, the electrostatic shielding effect of amino acids on the zinc anode surface and the interfacial adsorption of organophosphonic acids synergistically suppressed dendrite growth.

[0078] Comparative Example 5 is a conventional ionic hydrogel (without organophosphonic acid, nanoclay, multi-arm crosslinking agent, or amino acid additives), with an ionic conductivity of only 8.2 mS / cm, a compressive modulus of only 40 kPa, a cycle life of 185 hours, and an elongation at break of only 50% (high brittleness). Example 1 is significantly superior to Comparative Example 5 in terms of ionic conductivity, compressive modulus, elongation at break, and cycle life, demonstrating that the synergistic design of the hydrophilic monomer, multi-arm crosslinking agent, nanoclay, organophosphonic acid, and amino acid additives in this invention is not a simple superposition of the functions of each component, but rather works through multiple mechanisms of dispersion stabilization, dynamic crosslinking, ion conduction, and interface regulation.

[0079] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited to the embodiments described. Those skilled in the art can make various equivalent modifications or substitutions without departing from the spirit of the present invention, and these equivalent modifications or substitutions are all included within the scope defined by the claims of this application.

Claims

1. A hydrogel electrolyte, characterized in that, The raw materials for preparing the hydrogel electrolyte, by mass fraction, include: 5-20 parts of hydrophilic monomer, 0.5-5 parts of multi-arm crosslinking agent, 0.5-8 parts of nano-clay, 0.5-10 parts of organophosphonic acid, 5-30 parts of soluble zinc salt, 0.01-0.5 parts of photoinitiator, and 0.5-5 parts of amino acid additives; the hydrophilic monomer includes water-soluble monomers containing olefinic unsaturated bonds, and the multi-arm crosslinking agent includes star-shaped macromolecules with three or more polymerizable end groups.

2. The hydrogel electrolyte according to claim 1, characterized in that, The organophosphonic acid is adsorbed onto the surface of the nanoclay sheets, and the hydrophilic monomer and the multi-arm crosslinking agent are free radically polymerized to form a star-shaped crosslinking network. The nanoclay is dispersed in the star-shaped crosslinking network and forms a dynamic physical crosslinking network with the star-shaped crosslinking network.

3. The hydrogel electrolyte according to claim 1, characterized in that, The hydrophilic monomers include one or more of acrylamide, N-hydroxyethylacrylamide, N-isopropylacrylamide, acrylic acid, and alkali metal salts of acrylic acid.

4. The hydrogel electrolyte according to claim 1, characterized in that, The multi-arm crosslinking agent includes one or more of multi-arm polyethylene glycol acrylate, multi-arm polyethylene glycol methacrylate, and multi-arm acrylamide derivatives.

5. The hydrogel electrolyte according to claim 1, characterized in that, The nano-clay includes one or two of lithium saponite and organobentonite.

6. The hydrogel electrolyte according to claim 1, characterized in that, The organophosphonic acid includes one or more of ethylenediaminetetramethylenephosphonic acid, hydroxyethylidene diphosphonic acid, aminotrimethylenephosphonic acid, and 2-phosphonobutane-1,2,4-tricarboxylic acid; and / or the soluble zinc salt includes one or more of zinc sulfate, zinc acetate, zinc trifluoromethanesulfonate, zinc chloride, and zinc nitrate; and / or the amino acid additive includes one or more of alanine, β-alanine, proline, valine, glycine, lysine, and 6-aminohexanoic acid.

7. A method for preparing a hydrogel electrolyte as described in any one of claims 1 to 6, characterized in that, Includes the following steps: Nano-clay, water, and organophosphonic acid were mixed and stirred to disperse, resulting in an organophosphonic acid-clay composite dispersion. The organophosphonic acid-clay composite dispersion was mixed with soluble zinc salt, hydrophilic monomer, multi-arm crosslinking agent, amino acid additive, and photoinitiator, and stirred to obtain a precursor solution. The precursor solution was cured under ultraviolet light to obtain the hydrogel electrolyte.

8. The preparation method according to claim 7, characterized in that, The ultraviolet light curing wavelength is 300–400 nm, and the light intensity is 50–500 mW / cm². 2 The illumination time is 1 to 60 minutes.

9. An aqueous zinc-ion battery, characterized in that, Includes the hydrogel electrolyte according to any one of claims 1 to 6.

10. A flexible wearable electronic device, characterized in that, Including the aqueous zinc-ion battery as described in claim 9.